2001
DOI: 10.1053/euhj.1999.1938
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of cigarette smoking on platelet-dependent thrombin generation

Abstract: Platelet-dependent thrombin level is enhanced in smokers, even when not smoking, when compared with non-smokers and increases immediately after smoking. Increases in nicotine and cotinine levels caused by smoking induced a prothrombotic state in smokers via increased platelet-dependent thrombogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 27 publications
2
63
0
4
Order By: Relevance
“…It is noteworthy that exposure to some of these toxicants, albeit from traditional tobacco smoking and other sources, was found to be associated with an enhanced platelet activation phenotype 6. Furthermore, while the effects of nicotine on platelet activation/aggregation are still controversial,16, 105, 106, 107, 108 particulate matter109, 110 and acrolein93 were indeed found to enhance platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that exposure to some of these toxicants, albeit from traditional tobacco smoking and other sources, was found to be associated with an enhanced platelet activation phenotype 6. Furthermore, while the effects of nicotine on platelet activation/aggregation are still controversial,16, 105, 106, 107, 108 particulate matter109, 110 and acrolein93 were indeed found to enhance platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…3 Platelet-dependent thrombin generation is elevated in smokers even after they abstain from smoking for several hours. 4 It has been suggested that a higher number of active platelets in chronic smokers leads to increased thrombin generation and increased thrombotic risk. 5 Many studies, mainly of platelet aggregation in response to exogenous agonists like ADP and serotonin, show increased response after exposure to cigarette smoke.…”
mentioning
confidence: 99%
“…22,23 Trombosit bağımlı trombin düzeyi sigara içimi sonrası belirgin düzeyde artmaktadır. 24 Ayrıca sigara içiminin kan viskozitesinde doz bağımlı artışa neden olduğunu gösteren bir çalışma vardır. 7 Sigaranın tromboembolik olaylara ve vasküler dolaşım bozukluğuna neden olduğu öteden beri bilinen bir gerçektir.…”
Section: Discussionunclassified